Pendampingan Pembuatan Kamus Mufrodat dan Sinonimnya di Madrasah Diniyyah Nurul Huda Balung Jember - Zainuri, Zainuri; Wahyudi, Imam (An-Nuqthah, 2024)
The aim is to introduce students to actual mufrodat according to existing needs in Indonesia and its mufrodat to become a provision for academic careers, especially at Madrasah Diniyyah Nurul Huda Tutul Balung. The strategy adopted for this assistance is through the PAR (Participatory Action Research) method. This dictionary is generally suitable for beginners and anyone who wants to learn Arabic even if they are not fluent in Arabic. In this dictionary, apart from including new Arabic words, there are meanings that cannot be understood which cannot be known using the rules of sharaf science (wazan-wazan), but must come from the original Arabic language (sama'i words) which are remembered and heard. . In its structure, this dictionary defines mufrodat entries in the form of isim which is associated with the content of sentences and mufrodat entries are associated with fi'il sentences in the form of fi,il. By paying attention to the first letter of the vocabulary you want to search for and readers don't need to look for the root words of the vocabulary